2009
DOI: 10.1111/j.1524-4725.2009.01317.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic Studies of the Below-the-Knee Great Saphenous Vein after Endovenous Laser Ablation

Abstract: Based on this histopathologic study, acute thermal damage of the below-the-knee GSV after EVLA was limited to the intima and the inner third of the media. No acute damage of perivascular nerve tissue was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…4,12,1620 The change in the vein wall after EVLA with CW includes (1) carbonization, (2) homogeneous basophilic discoloration, (3) coagulation necrosis, and (4) loss of distinction between collagen and muscular bundles. 20 Fan and Rox-Anderson 5 said that proper EVLA histology using CW laser was collagen denaturing, but too much energy leads to bilateral charring, ablation, or perforation. The histological changes were different in EVLA using PW and CW in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…4,12,1620 The change in the vein wall after EVLA with CW includes (1) carbonization, (2) homogeneous basophilic discoloration, (3) coagulation necrosis, and (4) loss of distinction between collagen and muscular bundles. 20 Fan and Rox-Anderson 5 said that proper EVLA histology using CW laser was collagen denaturing, but too much energy leads to bilateral charring, ablation, or perforation. The histological changes were different in EVLA using PW and CW in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular perforation with subsequent perivascular bleeding was occasionally (<10%) seen in cases. 24…”
Section: Commentsmentioning
confidence: 99%
“…Tumescence anaes- thesia is applied and the laser treatment is conducted from proximally to distally. Histological studies have shown that the result of this acute thermic exposure is damage to the intima and the inner third of the media [31]. Three months after EVLA there is the endothelium is absent and an organised thrombus has formed in the lumen [32].…”
Section: Endovenous Laser Ablationmentioning
confidence: 99%